2018
DOI: 10.21608/jppp.2018.41386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Application of some Zinc and Phosphorus Sources on Controlling Helminthosporium Leaf Spot Disease and Production of Sesame

Abstract: Nineteen isolates of Helminthosporium sesami were obtained from infected sesame plants with Helminthosporium leaf spot taken from different locations in Nubaria region, El-Behera Governorate, Egypt. All the obtained isolates of the pathogen were able to infect Del Al-Jamal sesame variety plants causing Helminthosporium leaf spot disease symptoms with different degrees. The objectives of this study were to evaluate the efficiency of some zinc and phosphorus sources against the pathogen and their effect on some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Sodium bicarbonate is okay, but it is not as good (Kuepper et al 2001). Likewise, potassium phosphates proved to be effective against phytopathogenic fungi (Arslan 2015;El-Fawy and El-Said 2018). Yet, until recently, such safe salts have not been reported as management solutions for several apple diseases in Egypt (Youssef and Roberto 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sodium bicarbonate is okay, but it is not as good (Kuepper et al 2001). Likewise, potassium phosphates proved to be effective against phytopathogenic fungi (Arslan 2015;El-Fawy and El-Said 2018). Yet, until recently, such safe salts have not been reported as management solutions for several apple diseases in Egypt (Youssef and Roberto 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Matloob and Kim (2016) found that A. chroococcum bacteria could inhibit the pathogenic fungus R. solani growth by 100% on PSA medium.On the other hand Jaiswal et al (2018) indicated that the use of biochar at a concentration 3% resulted in improving cucumber plant resistance against root rot disease caused by Pythium aphanidermatum. El-Fawy and El-Said (2018) also found that foliar spraying of sesame plants with K 2 HPO 4 at a concentration 100 mM reduced the severity of leaf spot disease caused by Helminthosporium sesamiin in addition to increasing plant productivity .Therefore, this study aimed to evaluate the efficiency of some resistance induction agents in protecting soybean seedlings from infection by the pathogenic fungi and their effect on the growth of soybean plants.…”
Section: Introductionmentioning
confidence: 99%